Age model of sediment core PS75/054-1 - Loftfield, Julia; Nowaczyk, Norbert R; Lembke-Jene, Lester; Frederichs, Thomas; Lachner, Johannes; Lamy, Frank; Rugel, Georg; Stübner, Konstanze; Adolphi, Florian
Age model of PS75/054-1 21 – 66 ka BP. Model is based on correlating XRF scan derived elemental ratios and counts to δ18O and dust content of EDC (AICC2023) and correlation of paleomagnetic measurements to the Black Sea core stack of Liu et al. (2020).